A Hands-on Recommendation of Artificial Lighting for Promoting Product Appeal in Fresh Markets - Veerasilp, Warut; Sansena, Narumol (International Journal of Building, Urban, Interior and Landscape Technology, 2022)
This descriptive study aims to help sellers in fresh markets be aware of the importance of artificial lighting in promoting the appeal of their products and apply it at their stalls. This study was conducted in three stages, with two objectives, to 1) gain insights regarding types of artificial lights used at the stalls and common product types sold at the selected fresh markets, and 2) identify the artificial lighting that suits each type of the common products. Insights from four popular markets in Bangkok were gained during the Exploration Stage. Most sellers were using fluorescents in cool white, warm white, and mixed white, and incandescents provided by the market management. Vegetables, fruits, seafood, meats, and desserts were the common food products sold. The dimensions of the stalls at the markets were in a similar range. Such information was used to design mockup stalls at the Design Stage; they were installed with each type of artificial lighting. The mockups were used during the Testing Stage when the lighting was shining on the food products. The respondents rated that mix-white fluorescents helped vegetables, fruits, and seafood look appealing, and so did the warm white fluorescents for meats and desserts. The results of this study led to a recommendation addressing the Correlated Color Temperature effects on the appeal of products and how sellers can select off-the-shelf light bulbs suiting their products.